Coordinated Scheduling Strategy for Networked Microgrids Preserving Decision Independence and Information Privacy - Sun, Wenyao; Tian, Youwen; Zhao, Yi; Zhang, Haonan; Fu, Qiaochu; Li, Maolin (Frontiers in Energy Research, 2022)
With the increasing penetration of distributed renewable generations (DRGs), microgrids will play an important role in the future power system. This paper studies the coordinated scheduling strategy of networked microgrids with private data exchange lim-itations and local management independence. Based on an adaptive robust optimization method, a coordinated scheduling model of networked systems considering the uncertainty of renewable generations is established. Then distributed algorithms are de-veloped to meet the needs of data privacy protection of individual microgrids. The Augmented Lagrangian (AL) decomposition method decomposes the model into several sub-problems, and an alternate optimization method is developed to speed up the solution. Case studies demonstrate the effectiveness of the proposed model and the solution methods.